2008
DOI: 10.1161/circep.108.799619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electroanatomic Contact and Noncontact Mapping of Ventricular Scar in a Postinfarct Ovine Model With Intramural Needle Electrode Recording and Histological Validation

Abstract: Background-Substrate-based ablation is useful for nonhemodynamically tolerated postinfarct ventricular tachycardia. We assessed the accuracy of the CARTO contact and EnSite noncontact systems at identifying scar in a chronic ovine model with intramural plunge needle electrode recording and histological validation. Methods and Results-Scar mapping was performed on 8 male sheep with previous percutaneous-induced myocardial infarction. Up to 20 plunge needles were inserted into the left ventricle of each animal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…8 Unipolar electrograms have also been evaluated for substrate mapping. 9,[11][12][13][14] The amplitude of unipolar electrograms high-pass filtered at 1 Hz is threefold to fivefold greater than that of bipolar electrograms high-pass filtered at 30 Hz. In comparisons with infarct scars detected by magnetic resonance imaging, Codreanu et al 9 found that the best electrogram amplitude threshold for characterizing scar was 6.52 mV for unipolar electrograms and 1.54 mV for bipolar electrograms, and bipolar electrogram amplitude was a better discriminator of scar.…”
Section: Substrate Mappingmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Unipolar electrograms have also been evaluated for substrate mapping. 9,[11][12][13][14] The amplitude of unipolar electrograms high-pass filtered at 1 Hz is threefold to fivefold greater than that of bipolar electrograms high-pass filtered at 30 Hz. In comparisons with infarct scars detected by magnetic resonance imaging, Codreanu et al 9 found that the best electrogram amplitude threshold for characterizing scar was 6.52 mV for unipolar electrograms and 1.54 mV for bipolar electrograms, and bipolar electrogram amplitude was a better discriminator of scar.…”
Section: Substrate Mappingmentioning
confidence: 96%
“…In an ovine infarct model, scar was better correlated with bipolar filtered as compared to unipolar minimally filtered electrogram amplitude. 12 At present, bipolar electrograms are preferred for defining endocardial scar.…”
Section: Substrate Mappingmentioning
confidence: 99%
“…Areas of interest show reduced EG amplitude in voltage maps and are considered a surrogate of myocardial scar. 2,3 An accurate high-density map of low voltage areas is key in identifying slow conduction zones inside the scar, also called conducting channels (CC). These CC display a higher voltage amplitude than the surrounding area and are the target for ablation in scar-related VTs.…”
mentioning
confidence: 99%
“…We have previously compared DSM with CARTO contact electrograms and validated the DSM scar localization with needle recordings and histology. 17 Use of DSM allows VT activation to be viewed over low-voltage substrate marked on the electroanatomic geometry, showing the relationship of the arrhythmic circuit to areas of scar. Generation of DSM is also faster than contact voltage maps because individual points do not require verification.…”
Section: Sivagangabalan Et Al Biventricular Mapping and Ablation Of Smentioning
confidence: 99%